PRINCIPLE FOR DETERMINING THE LEVEL OF REWARD OPERATOR URBAN PUBLIC TRANSPORT - Poliak, Milos; Kostalova, Katarina (Doprava a spoje, 2010)
The paper deals with methods of determining a reasonable profit. It is based on Regulation (EC). 1370/2007. The paper analyzes methods determining of reasonable profit in the following countries: Poland, France, Germany, Switzerland, Netherlands, UK and Spain. Analyzed on the basis of experience it can be stated that the payment is usually associated with some level of risk carrier, whereas transport as such carries the risk.